Treatment outcome of pediatric tuberculosis in eastern Ethiopia - Weldegebreal, Fitsum; Teklemariam, Zelalem; Mitiku, Habtamu; Tesfaye, Tamrat; Abrham Roba, Aklilu; Tebeje, Fikru; Asfaw, Abiyot; Naganuri, Mahantash; Jinnappa Geddugol, Bahubali; Mesfin, Frehiwot; Abdulahi, Ibsa Mussa; Befikadu, Hilina; et al. (Frontiers in Pediatrics, 2022)
Background: Children are susceptible to infection with Mycobacterium tuberculosis in the community and at a greater risk of progressing to active disease. It causes significant childhood mortality and morbidity. However, the contribution of childhood tuberculosis (TB) as well as its treatment outcomes is not well documented and no research has been done in eastern Ethiopia. Objective: To assess the treatment outcome and its predicators of childhood Tuberculosis in eastern Ethiopia from September 1, 2017 to January 30, 2018 Methods: A retrospective study was conducted in eight selected hospitals in eastern Ethiopia. Data on 2002 children with tuberculosis was extracted by using the standard checklist of the national tuberculosis treatment format. Treatment outcomes were determined according to the standard definitions of the National Tuberculosis and Leprosy Control Programme. Data were entered into Epi Data software version 3.1 and exported to Statistical Package for Social Science version 20 for analysis. Bivariate and multivariable regression analyses were carried out to examine the associations between dependent and independent variables. A P-value of <0.05 was considered statistically significant. Result: The overall successful treatment rate was 1774 (88.6%) 95% CI (80.59-97.40). A total of 125 (6.2%), 1648 (82.3%), 59 (2.9%), and 19 (0.9%) of children with TB were cured, completed, defaulted, and died, respectively. The high number of defaulters and deaths were reported in the age group <10 years. More children with smear positive pulmonary TB (74.4%) were cured, while smear negative tuberculosis had higher treatment completion rates (Table 3). Being male in sex (AOR: 0.71, 95% CI: 0.53, 0.96) and those with HIV positive sero status (AOR: 0.51, 95% CI: 0.29, 0.90) had a lower chance of a successful treatment outcome. Conclusion: The treatment success rate was higher than the recent WHO report. Those male and HIV seropositive status were less likely to have a successful treatment outcome. Therefore, efforts should be made by each health institution in eastern Ethiopia by giving emphasis to male and HIV positive individuals. Key words: treatment outcome, childhood Tuberculosis, eastern Ethiopia